Schuldbekenntnis und Vergebungsbitten des Papstes in theologischer Perspektive - Hercsik, Donath (Zeitschrift für katholische Theologie, 2001)
The Great Jubilee 2000 should become a feast founded in pardon and reconciliation. Already 1994 Pope John Paul II called up everyone to examine his conscience and to purify his memory. The whole church should prepare herself in regard mainly to anti-judaisme, inquisition and reception of II° Vatican Council. The main-event was the liturgical act of penance in Rome the first Quadragesima Sunday of the Holy Year with the seven confessions and forgiving-prayers formulated by the Pope and other church-dignitaries. How we must judge theologically this acknowledgement of fault in the past? The article deals with seven problems in this context showing that the fact is not only theologically right, but explains also as a hermeneutical key a better understanding of the present pope's understanding of his ministry.